Assessing the role of informal sector in WEEE management systems: A System Dynamics approach. (November 2016) - Ardi, Romadhani; Leisten, Rainer
Highlights: This study models the existences of informal recycling sector using System Dynamics. This study hypothesizes the endogenous dynamics existing within the informal sector. This study found the impact of the dynamics on the overall WEEE management systems. The significant role of secondary market to the informal sector is revealed. Abstract: Generally being ignored by academia and regulators, the informal sector plays important roles in Waste Electrical and Electronic Equipment (WEEE) management systems, especially in developing countries. This study aims: (1) to capture and model the variety of informal operations in WEEE management systems, (2) to capture the dynamics existing within the informal sector, and (3) to assess the role of the informal sector as the key player in the WEEE management systems, influencing both its future operations and its counterpart, the formal sector. By using System Dynamics as the methodology and India as the reference system, this study is able to explain the reasons behind, on the one hand, the superiority of the informal sector in WEEE management systems and, on the other hand, the failure of the formal systems. Additionally, this study reveals the important role of the second-hand market as the determinant of the rise and fall of the informal sector in the future.